Práticas de conciliação de conflitos individuais na Justiça do Trabalho: uma reflexão sob a perspectiva do juiz conciliador - Salles, Juliana Petenate (2022)
Despite the historical mission of the Labor Courts to settle conflicts, the conciliation process has always been challenging, especially considering that it may involve rights that are mostly unwaivable. This study is intended, in a first stage, to establish the foundation for the reflection on its central matter: how can a conciliation process be developed in harmony with the principle of unwaivability of labor rights, in a scenario of risks, and how to face the challenges imposed by the factual reality? After the determination of the parameters for the qualitative analysis on how conciliation sessions are conducted, labor hearings conducted by appellate judges in Ruy Barbosa Courthouse of the Appellate Labor Court of the 2nd Region were observed and a critical analysis of the strategies and methods adopted during the conduct of the conciliation process was made. The purpose was to extract the good practices of the judge who conducted the conciliation process and propose reflections on some of the challenges empirically observed. In order to do so, the perspective of the court was adopted.